Metal Salen- and Salphen-Containing Organic Polymers: Synthesis and Applications - Elbert, Sven M.; Mastalerz, Michael (Organic Materials, 2020)
The properties of organic polymeric materials can be chemically fine-tuned by the implementation of functional groups or units within the backbone. Especially the inclusion of coordinated metal centers offers a nearly infinite toolbox to adjust properties and thus potential applications. In particular, salen and salphen complexes are widely known to be highly efficient homogenous catalysts. They are also used as luminescent materials and devices or as supramolecular building blocks. This review focusses on the class of salen- and salphen-containing organic polymers, from 1D to 3D. Besides the comparison of synthetic polymerization methods, properties and applications are discussed, with an emphasis on porous 2D and 3D polymeric metal salphens and salens for heterogeneous catalysis and gas sorption.
Keywords: Porous polymers; heterogeneous catalysis; conductive films; salens; salphens; gas sorption